KONTRIBUSI KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA-TANGAN DENGAN HASIL FREE THROW PADA TIM BASKET PUTRA SMP NEGERI 8 PEKANBARU - Siddik, Pahmus; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : This research is intended to see the contribution of elasticity of wrist and hand-eye coordination with the result of free throw on male students basketball team of SMP Negeri 8 Pekanbaru.The purpouse of this research also to train student so they can do free throw with good method and maximal result. This research using experimental method with male stundent basketball team of SMP Negeri 8 Pekanbaru as the population, sample in this research is all population that contain 12 student. Instrument that has beed used in this research is eleasticity test of wirst, throw and cacth tennis ball, and free throe test, to measure shooting skill when doing free throw. After that, data counted with statistic, to examine normality with lilifors test on significant level of Î± (0,05). The Hypothesis of this research shows there is correlation and contrbution of elasticity of wrist and hand-eye coordinataion with free throw result. As the result of this research with statistic procedure, researcher finds conclution that is correlation about elasticity of wrist and hand-eye coordination with free throw result, with calculating result the contribution of elasticity of wrist with free throw skill is 81,00%, contribution of hand-eye coordination with free throw skill is 65,61% and contribution of elasticity of wrist and hand-eye coordination with free throw skill is 38,44%.Key word : wrist flexibility and hand-eye coordination, free throw